1998
DOI: 10.1523/jneurosci.18-04-01363.1998
|View full text |Cite
|
Sign up to set email alerts
|

Bax Involvement in p53-Mediated Neuronal Cell Death

Abstract: The tumor suppressor gene p53 has been implicated in the loss of neuronal viability, but the signaling events associated with p53-mediated cell death in cortical and hippocampal neurons are not understood. Previous work has shown that adenovirus-mediated delivery of the p53 gene causes cortical and hippocampal neuronal cell death with some features typical of apoptosis. In the present study we determined whether p53-initiated changes in neuronal viability were dependent on members of the Bcl-2 family of cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
276
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(303 citation statements)
references
References 88 publications
23
276
4
Order By: Relevance
“…Induction of p53 is associated with a rapid increase in its levels and with an increased ability to bind DNA and mediate transcriptional activation (Lakin and Jackson, 1999). The products encoded by p53 can regulate the expression of Bax, which may mediate p53-dependent cell apoptosis (Xiang et al, 1998;Chen et al, 2005a,b). It was reported that p53 might lead to apoptosis indirectly by down-regulating expression of bcl-2 (Miyashita et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of p53 is associated with a rapid increase in its levels and with an increased ability to bind DNA and mediate transcriptional activation (Lakin and Jackson, 1999). The products encoded by p53 can regulate the expression of Bax, which may mediate p53-dependent cell apoptosis (Xiang et al, 1998;Chen et al, 2005a,b). It was reported that p53 might lead to apoptosis indirectly by down-regulating expression of bcl-2 (Miyashita et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…36 Of the proapoptotic members of the Bcl-2 family, Bax is considered to be the most significant mediator of mitochondria-dependent apoptosis in neurons. 29,30 The contribution of Bak to neuronal apoptosis depends on the cell type and apoptotic stimulus. 28 Bax deficiency alone partially protects primary telencephalic NPCs against DNA damage-induced death; however, dual Bax and Bak deficiency provides an even greater protective effect against this apoptotic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The proapoptotic molecules Bax and Bak play overlapping functions in the regulation of apoptosis, and it appears that the significance of either molecule is highly dependent on cell type. 11,[28][29][30] We reasoned that either Bax or Bak might be critical for the activation of the intrinsic apoptotic pathway in NPCs. To test this hypothesis, we crossed mice that were heterozygous for both bax and bak and prepared FGF2-expanded NPCs from E13 embryos.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional induction and/or the posttranslational activation of Bcl-2 homology domain 3 (BH3)-only proteins is believed to be essential for Bax/Bak activation and downstream signaling events. Previous studies have demonstrated that apoptotic excitotoxic injury is inhibited by loss of Bax or Bcl-2 overexpression (Xiang et al, 1998;Wang et al, 2004;Dietz et al, 2007;Semenova et al, 2007). In this study, we demonstrate that, in contrast to currently held views, ATP depletion and energy stress signaling are not only responsible for the activation of necrotic but also for the activation of apoptotic excitotoxic injury and that this occurs via the activation of an AMP-activated protein kinase (AMPK), culminating in the activation of the BH3-only protein Bim.…”
Section: Bim Mediates Excitotoxic Apoptosismentioning
confidence: 99%